Study of Role and Goals of NGOs in Haryana on Social and women development - Rani, Meenu (Universal Research Reports, 2018)
NGOs are bodies that develop team work towards achieving some common objectives. The most common areas.in which the NGOs are working is health, education, employment, empowerment, women issues etc. NGOs function as relief and welfare agents and sometimes as public servants and also as promoters of grass-root level development, self-help and. empowerment movements. They also contribute towards technological development and innovative work.